2021
DOI: 10.1101/2021.02.22.432214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kynurenine pathway in post-mortem prefrontal cortex and cerebellum in schizophrenia: relationship with monoamines and symptomatology

Abstract: Background: the cortico-cerebellar-thalamic-cortical circuit has been implicated in the emergence of psychotic symptoms in schizophrenia (SZ). The kynurenine pathway (KP) has been linked to alterations in glutamatergic and monoaminergic neurotransmission and to SZ symptomatology through the production of the metabolites quinolinic acid (QA) and kynurenic acid (KYNA). Methods: this work describes alterations in KP in the post-mortem prefrontal cortex (PFC) and cerebellum (CB) of 15 chronic SZ patients and 14 co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Thus, inflammatory processes could alter myelinization and lead to neuronal connectivity dysfunction. The involvement of immune dysfunction and inflammation in SZ is supported by emerging evidence suggesting aberrant immune mechanisms (O'Donnell et al, 1995;Kroken et al, 2019;Comer et al, 2020;Afia et al, 2021). A genome-wide association study reported a major histocompatibility complex (MHC) locus and Toll-like receptors (TLRs), both involved in innate immunity, as genetic risks for SZ (Bramon et al, 1038).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, inflammatory processes could alter myelinization and lead to neuronal connectivity dysfunction. The involvement of immune dysfunction and inflammation in SZ is supported by emerging evidence suggesting aberrant immune mechanisms (O'Donnell et al, 1995;Kroken et al, 2019;Comer et al, 2020;Afia et al, 2021). A genome-wide association study reported a major histocompatibility complex (MHC) locus and Toll-like receptors (TLRs), both involved in innate immunity, as genetic risks for SZ (Bramon et al, 1038).…”
Section: Introductionmentioning
confidence: 99%